Root rot in medicinal plants: a review of extensive research progress - Han, Yu; Sun, Tianqi; Tang, Yuman; Yang, Min; Gao, Weiwei; Wang, Lihong; Sui, Chun (Frontiers in Plant Science, 2025)
Root rot is a general term for soil-borne diseases that cause the necrosis and decay of underground plant parts. It has a wide host range and occurs in various types of plants, including crops, horticultural crops and medicinal plants. Due to the fact that medicinal plants generally have a long growth cycle and are primarily the root and rhizome herbs. This results in root rot causing more serious damage in medicinal plant cultivation than in other plants. Infected medicinal plants have shrivel or yellowed leaves, rotting rhizomes, and even death of the entire plant, resulting in a sharp decline in yield or even total crop failure, but also seriously reduce the commercial specifications and effective ingredient content of medicinal plants. The pathogens of root rot are complex and diverse, and Fusarium fungi have been reported as the most widespread pathogen. With the expansion of medicinal plant cultivation, root rot has occurred frequently in many medicinal plants such as Araliaceae, Fabaceae, Ranunculaceae, and Solanaceae and other medicinal plants. This article reviews recent research progress on root rot in medicinal plants, covering various aspects such as disease characteristics, occurrence, pathogen species, damage to medicinal plants, disease mechanisms, control measures, and genetic factors. The aim is to provide reference for better control of root rot of medicinal plants.